Fast and efficient electrocatalytic oxidation of glucose triggered by Cu2O-CuO nanoparticles supported on carbon nanotubes - Wang, Zhongting; Liu, Yi; Cheng, Yongxi; Men, Yu-Long; Liu, Peng; Zhang, Lei; Dai, Bin; Pan, Yun-Xiang (Frontiers in Chemistry, 2022)
Electrocatalytic glucose oxidation reaction (GOR) is the key to construct sophisticated devices for fast and accurately detecting trace glucose in blood and food. Herein, a noble-metal-free Cu/C-60 catalyst is fabricated by supporting Cu2O-CuO nanoparticles on carbon nanotubes through a novel discharge process. For GOR, Cu/C-60 shows a sensitivity as high as 532 μA mM−1 cm−2, a detection limit as low as 1 μM and a steady-state response time of only 5.5 s. Moreover, Cu/C-60 has outstanding stability and anti-interference ability to impurities. The synergistic effect of Cu2O-CuO could improve the adsorption and conversion of glucose, thus enhancing GOR performance. By using Cu/C-60, we fabricate a three-electrode chip. A portable and compact electrochemical system is constructed by connecting the three-electrode chip with Cu/C-60 to an integrated circuit board and a mobile phone for recording and displaying data. The portable and compact electrochemical system results in a GOR sensitivity of 501 μA mM−1 cm−2, which is close to the data measured on the bloated electrochemical workstation. The detection limit of the portable and compact electrochemical system in GOR is 50 μM. This is higher than those obtained on the bloated electrochemical workstation, but is much lower than the common blood glucose concentration of human body (>3 mM). This demonstrates the accuracy, reasonability and applicability of the portable and compact electrochemical system. The results of the present work are helpful for fabricating fast, efficient and portable devices for detecting trace amount of glucose in blood and food.